Students’ Perspective on the Use of Edmodo as an Assessment Tool - Fauzul Etfita (J-SHMIC : Journal of English for Academic, 2019)
The lecturers are in search of exploring innovative assessment techniques in order to promote students skill. For assessing students’ language skills, the study introduces Edmodo. Being a web-based online technology, beside can provide all subject, Edmodo also allows students and teacher to post materials, share videos and links, grades, notices, and assignment. It enables teachers to work with their learners in real time, and can be used either in the class or at home. The special code assigned for a particular group which makes it secure and safe in use. The study focuses on how the use of edmodo as an assessment tool. 68 students from two classes that attending News and Report Writing Course in English Language Education Islamic University of Riau in Pekanbaru participated in various assessment activities through Edmodo during 2016/2017 academic year. Reflection of the students regarding the use of Edmodo as an assessment tool were obtained by semi-structured interviews. There were four questions which posed to the students conducted by the researcher. The result indicated that most of the students motivated and Edmodo also reduced their test anxiety to a great extent and they would prefer to be assessed through Edmodo rather than traditional asessment techniques like pen-and-paper test.